2015
DOI: 10.1097/01.j.pain.0000460351.30707.c4
|View full text |Cite
|
Sign up to set email alerts
|

Shp-1 dephosphorylates TRPV1 in dorsal root ganglion neurons and alleviates CFA-induced inflammatory pain in rats

Abstract: Transient receptor potential vanilloid 1 (TRPV1) receptors are expressed in nociceptive neurons of rat dorsal root ganglions (DRGs) and mediate inflammatory pain. Nonspecific inhibition of protein-tyrosine phosphatases (PTPs) increases the tyrosine phosphorylation of TRPV1 and sensitizes TRPV1. However, less is known about tyrosine phosphorylation's implication in inflammatory pain, compared with that of serine/threonine phosphorylation. Src homology 2 domain-containing tyrosine phosphatase 1 (Shp-1) is a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…H + can be generated by activating the outer peripheral nociceptors, which have an important role in inflammatory pain. During inflammatory pain conduction, noxious stimulation signals are transmitted by the primary sensory neurons in trigeminal ganglia (TG) and dorsal root ganglion to the dorsal horn of the lumbar spinal cord by synaptic transmission (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…H + can be generated by activating the outer peripheral nociceptors, which have an important role in inflammatory pain. During inflammatory pain conduction, noxious stimulation signals are transmitted by the primary sensory neurons in trigeminal ganglia (TG) and dorsal root ganglion to the dorsal horn of the lumbar spinal cord by synaptic transmission (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Transient receptor potential vanilloid receptor 1 (TRPV1) plays an important role in both itch transduction and pain, specifically heat pain. The TRPV1 channel is activated by temperatures in the noxious range (> 42 °C) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the histaminergic itch provocation itself establishes neurogenic inflammation in the area, which has been shown not to differ when heat pain is applied. 21 Transient receptor potential vanilloid receptor 1 (TRPV1) plays an important role in both itch transduction [22][23][24][25][26] and pain, [27][28][29][30][31][32][33] specifically heat pain. The TRPV1 channel is activated by temperatures in the noxious range (> 42°C).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was shown that Src‐mediated phosphorylation of TRPV1 at Tyr200 leads to modulation of subcellular trafficking of TRPV1 to the plasma membrane (X. Zhang, Huang, & McNaughton, ). On the other hand protein tyrosine phosphatase (PTP) Shp‐1 dephosporylates TRPV1 in dorsal root ganglion (DRG) neurons and reduces the inflammatory pain in rats, induced by Complete Freund's adjuvant (Xiao et al, ). Similarly, TRPV4 phosphorylation by Src family kinases, in different cell lines has been reported.…”
Section: Introductionmentioning
confidence: 99%